Antenatal Care for High Risk Pregnancy - Ali Sungkar; Raymond Surya (Cermin Dunia Kedokteran, 2020)
Despite 38% gradual fall since 2000, there was still approximately 295,000 women died during and following pregnancy and childbirth in 2017. Factors that lead to high maternal mortality include inequality access to health service, severe bleeding (mostly postpartum hemorrhage), infection, high blood pressure during pregnancy, complication from delivery, and unsafe abortion. These deaths are correlated to delay in decision to seek care, delay in reaching care, delay in receiving adequate health care. Improvement of antenatal care was the solution to this problem. Indonesia has not updated to the newest model of WHO antenatal care in 2016. Defining high-risk and updating the model can help Indonesia provides excellent care for mothers and reduce maternal deaths. Meskipun terdapat penurunan angka kematian ibu (AKI) sebesar 38% sejak tahun 2000, 295.000 wanita meninggal peripartum pada tahun 2017. Faktor yang menyebabkan AKI di antaranya tidak meratanya akses pelayanan kesehatan, perdarahan berat, infeksi, tekanan darah tinggi selama kehamilan, komplikasi persalinan, dan aborsi tidak aman. Kematian ini terkait dengan keterlambatan keputusan untuk merujuk, keterlambatan untuk mencapai tempat rujukan, dan keterlambatan mendapatkan tatalaksana yang baik. Hingga saat ini, Indonesia belum mengikuti panduan kunjungan antenatal terbaru dari WHO tahun 2016. Mendefinisikan kehamilan risiko tinggi dan penyesuaian model kunjungan antenatal diharapkan dapat memberikan perawatan yang baik bagi ibu dan menurunkan kematian maternal.